Impact of self-inflicted injury on nontherapeutic laparotomy in patients with abdominal stab wounds. Issue 9 (September 2018) - Matsumoto, Shokei; Hayashida, Kei; Furugori, Shintaro; Shimizu, Masayuki; Sekine, Kazuhiko; Kitano, Mitsuhide
Abstract: Introduction: Because Japan has high suicide rates and low violent crime rates, it is likely that most abdominal stab wounds (ASWs) in Japan are self-inflicted. Although physical examination is one of the most important factors in surgical decision making, such evaluations can be difficult in patients with self-inflicted ASWs due to patient agitation and uncooperative behavior. Therefore, the self-inflicted nature of an injury may strongly affect clinical practice, particularly in Japan, but its influence remains uncertain. We hypothesized that the rates of exploratory laparotomy and nontherapeutic laparotomy (NTL) would be higher in self-inflicted patients. Methods: We reviewed ASW patients from 2004 to 2014 in the Japan Trauma Data Bank. The rates of exploratory laparotomy and NTL were compared between self-inflicted and non-self-inflicted ASWs. Results: Of the 1705 eligible patients, 1302 patients (76.4%) had self-inflicted ASWs, and 403 patients (23.6%) had non-self-inflicted ASWs. Self-inflicted patients had a significantly higher rate of psychiatric history, but lower injury severity. The in-hospital mortality rate was similar between the two groups (4.5% vs. 5.2%, p = 0.576). Self-inflicted patients had significantly higher rates of exploratory laparotomy and NTL (69.1% vs. 56.7%, p < 0.001, 22.5% vs. 13.6%, p = 0.03, respectively). Self-inflicted patients were also associated with significantly longer hospital stays (10.0 [5.0–21.0] vs. 9.0 [4.0–18.0] days, P = 0.045). In a multivariable analysis, self-inflicted patients were independently associated with exploratory laparotomy (odds ratio [OR], 2.05; 95% confidence interval [CI]: 1.55–2.72) and NTL (OR, 1.61; 95% CI: 1.01–2.56). Conclusion: ASWs in Japan were predominantly self-inflicted. The clinical patterns of self-inflicted ASWs had some unique features. Patients with self-inflicted ASWs had higher rates of laparotomy and NTL. Further studies are needed to develop a useful protocol specific to self-inflicted ASWs.